Preliminary Concentration of Skim Latex and Its Wastewater Use Plate Sheet Microfiltration - Danteravanich, S.; Chalermpong, I.; Sridang, P.; Winsunthorn, S. (Journal of Applied Membrane Science & Technology, 2017)
Skim latex is a by–product of the concentrated latex factory. In this study, plate sheet membrane and cross–flow microfiltration (MF) experiments on skim latex and its wastewater were carried out to initially identify the performance of membrane separation. The series of MF experiments were conducted by using a nitrocellulose plate sheet membrane with a pore size of 0.1 μm and 0.45 μm at the pressures driven at 0.5 and 1 bar. The skim latex, skim latex diluted with water and skim rubber wastewater were tested by membrane separation. Sodium dodecyl sulfate (SDS) and cationic polymer were also added to the skim latex and used to combine it with the membrane. The results implied that filtration of skim rubber wastewater with a 0.45 μm membrane at 1 bar pressure gave the highest flux of 152.6 l/m2–hr while the skim latex gave the highest flux of only 1.4 l/m2–hr. When SDS and cationic polymer at 8 mg/l were added to the skim latex and tested, the highest flux was observed to increase as 2.1 and 2.8 l/m2–hr, respectively. When skim latex diluted with 5 and 10 times the amount of water was tested, the highest flux was determined to be 13.9 and 20.8 l/m2–hr, respectively. Using MF to filtrate the skim latex gave 48% SCOD removal. This result reflects that the MF system might be an alternative technology applied in the concentrated latex factory, especially to the rubber skim process.